Efektivitas model pembelajaran kooperatif tipe Think Pair Share (TPS) dan Numbered Head Together (NHT) berbantuan CD pembelajaran terhadap hasil belajar matematika - Dhestha Hazilla Aliputri; Bambang Suteng Sulasmono; Eunice Widyanti Setyaningtyas (Math Didactic: Jurnal Pendidikan Matematika, 2019)
The purpose of this study was to determine the effectiveness of the cooperative learning model Numbered Head Together (NHT) and Think Pair Share (TPS) to compare which one the effective model in terms of learning outcomes. This study consisted of two stages, namely pre-test and post-test. The pre-test phase was carried out to find out the Mathematics learning outcomes before treatment for homogeneity tests and normality tests a reference for testing hypotheses, while post-tests were conducted to find out the learning outcomes data after treatment. The subjects of this study were fourth grade students of SD N 1 Wulung District of Randublatung, Blora Regency. To help with the processing of data, researchers used the help of SPSS version 16. Based on the results of this study it was found that the use of NHT learning model was more effective than TPS in terms of Mathematics learning outcomes. This can be seen from the results of the analysis of data obtained by the results that the value of Asymp. Sig. (2-tailed) is 0.029 then 0.029 5 0.05 so Ha is rejected and Ho is accepted. It can be concluded that the learning model in the experimental class using NHT learning model is more effective than using TPS in the control class.